Cost-effectiveness of an enhanced Paramedic Acute Stroke Treatment Assessment (PASTA) during emergency stroke care: Economic results from a pragmatic cluster randomized trial. Issue 3 (March 2022) - Bhattarai, Nawaraj; Price, Christopher I; McMeekin, Peter; Javanbakht, Mehdi; Vale, Luke; Ford, Gary A; Shaw, Lisa
Background: The Paramedic Acute Stroke Treatment Assessment (PASTA) trial evaluated an enhanced emergency care pathway which aimed to facilitate thrombolysis in hospital. A pre-planned health economic evaluation was included. The main results showed no statistical evidence of a difference in either thrombolysis volume (primary outcome) or 90-day dependency. However, counter-intuitive findings were observed with the intervention group showing fewer thrombolysis treatments but less dependency. Aims: Cost-effectiveness of the PASTA intervention was examined relative to standard care. Methods: A within trial cost-utility analysis estimated mean costs and quality-adjusted life years over 90 days' time horizon. Costs were derived from resource utilization data for individual trial participants. Quality-adjusted life years were calculated by mapping modified Rankin scale scores to EQ-5D-3L utility tariffs. A post-hoc subgroup analysis examined cost-effectiveness when trial hospitals were divided into compliant and non-compliant with recommendations for a stroke specialist thrombolysis rota. Results: The trial enrolled 1214 patients: 500 PASTA and 714 standard care. There was no evidence of a quality-adjusted life year difference between groups [0·007 (95% CI: −0·003 to 0·018)] but costs were lower in the PASTA group [−£1473 (95% CI: −£2736 to −£219)]. There was over 97.5% chance that the PASTA pathway would be considered cost-effective. There was no evidence of a difference in costs at seven thrombolysis rota compliant hospitals but costs at eight non-complaint hospitals costs were lower in PASTA with more dominant cost-effectiveness. Conclusions: Analyses indicate that the PASTA pathway may be considered cost-effective, particularly if deployed in areas where stroke specialist availability is limited. Trial Registration: ISRCTN12418919www.isrctn.com/ISRCTN12418919